Accelerating nearest neighbor partitioning neural network classifier based on CUDA. (February 2018) - Wang, Lin; Zhu, Xuehui; Yang, Bo; Guo, Jifeng; Liu, Shuangrong; Li, Meihui; Zhu, Jian; Abraham, Ajith
Abstract: The nearest neighbor partitioning (NNP) method is a high performance approach which is used for improving traditional neural network classifiers. However, the construction process of NNP model is very time-consuming, particularly for large data sets, thus limiting its range of application. In this study, a parallel NNP method is proposed to accelerate NNP based on Compute Unified Device Architecture(CUDA). In this method, blocks and threads are used to evaluate potential neural networks and to perform parallel subtasks, respectively. Experimental results manifest that the proposed parallel method improves performance of NNP neural network classifier. Furthermore, the application of parallel NNP in performance evaluation of cement microstructure indicates that the proposed approach has favorable performance.